2010
DOI: 10.1192/bjp.bp.109.069617
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a stepped care intervention to prevent depression and anxiety in late life: randomised trial

Abstract: BackgroundThere is an urgent need for the development of cost-effective preventive strategies to reduce the onset of mental disorders.AimsTo establish the cost-effectiveness of a stepped care preventive intervention for depression and anxiety disorders in older people at high risk of these conditions, compared with routine primary care.MethodAn economic evaluation was conducted alongside a pragmatic randomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 12 publications
1
78
1
2
Order By: Relevance
“…Little information is available about how stepped care should be effectively implemented [22] and only a few randomized trials present convincing evidence and evaluations of both the cost and clinical effectiveness of this stepped-care model. Most studies investigated either the cost effectiveness [47,48] or the clinical effectiveness [49][50][51][52] of stepped care. When simultaneously investigated, the studies examined the effectiveness of a stepped-care model for patients with either a mood disorder [53] or an anxiety disorder [54], and only in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available about how stepped care should be effectively implemented [22] and only a few randomized trials present convincing evidence and evaluations of both the cost and clinical effectiveness of this stepped-care model. Most studies investigated either the cost effectiveness [47,48] or the clinical effectiveness [49][50][51][52] of stepped care. When simultaneously investigated, the studies examined the effectiveness of a stepped-care model for patients with either a mood disorder [53] or an anxiety disorder [54], and only in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we have to compare our results with other cost-effectiveness studies on early interventions to prevent depression in older adults-which are also rather scarce. A recent study found that a stepped-care approach might be cost-effective in preventing depression and anxiety in later life (van't Veer-Tazelaar et al, 2010). So it might be worth investigating if life-review is more cost-effective when offered as a second or third step in a stepped-care framework.…”
Section: Main Findingsmentioning
confidence: 97%
“…However, the added value of a stepped care approach has been demonstrated in other fields, such as in the prevention of depression and anxiety. 3,4 Also, a stepped care intervention programme showed positive effects on the outcome of care in depressed older people, which were better physical function and enhanced quality of life, 5 and the cost-effectiveness of a stepped care programme has been established in people with a depressive disorder in primary care. 6,7 In line with those findings, it was assumed that implementation of the SCS in primary care would improve adequate healthcare use and, ultimately, health outcomes.…”
Section: Porcheret Et Almentioning
confidence: 99%